Investigating the Needs of Technical Communication for TVET Students: A Case Study of Manufacturing Students in the Central Part of China - Luo, Mingdan; Alias, Norlidah; DeWitt, Dorothy (Journal of Technical Education and Training, 2022)
The most significant challenge in the 21st century is to prepare professionals to communicate technical information well through writing and speaking in the professional context. Research and studies on TC started to emerge in various aspects, but there is still scarcity in studies on curriculum design of TC. This paper explored the needs of curriculum design for TC at vocational colleges. The study was conducted in two steps: online questionnaires (n = 580) for students and semi-structured interviews (n=8) for English instructors at vocational colleges in the Central Part of China. The results showed that the manufacturing students had been taught less related TC skills in English subject, especially oral TC skills; however, the skills they most want to improve are team communication skills and oral TC skills. The findings also indicated that the current existing English courses in TVET institutions are irrelevant to TC skills on the one hand, but both the students and English instructors highly valued the importance of the TC module on the other hand. The findings from the current study serve as a basis for the curriculum design for TVET students. Further, this study may also contribute to the under-researched issue of English language learning in TVET institutions.